2001
DOI: 10.1073/pnas.211440298
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond dynamics of a drug–protein complex: Daunomycin with Apo riboflavin-binding protein

Abstract: In this contribution, we report studies of the primary dynamics of the drug-protein complexes of daunomycin with apo riboflavinbinding protein. With femtosecond resolution, we observed the ultrafast charge separation between daunomycin and aromatic amino acid residues of the protein, tryptophan(s). Electron transfer occurs from tryptophan(s) to daunomycin with two reaction times, 1 ps and 6 ps, depending on the local complex structure. The formation of anionic daunomycin radical is crucial for triggering a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…This interaction is reminiscent of the substrate pocket of riboflavin-binding protein in which the ligand riboflavin forms a compact stack between Trp-156 and Tyr-75 with equal interplanar distances of 3.7 Å (40, 41). DNR and riboflavin have similar planar three-ring anthraquinone-type structures, and it has been suggested that DNR inserts in the riboflavin-binding protein-binding site (42). The distribution of the spin label quenching sites, particularly along helix 3, reflects a diffuse location of bound DNR.…”
Section: Discussionmentioning
confidence: 99%
“…This interaction is reminiscent of the substrate pocket of riboflavin-binding protein in which the ligand riboflavin forms a compact stack between Trp-156 and Tyr-75 with equal interplanar distances of 3.7 Å (40, 41). DNR and riboflavin have similar planar three-ring anthraquinone-type structures, and it has been suggested that DNR inserts in the riboflavin-binding protein-binding site (42). The distribution of the spin label quenching sites, particularly along helix 3, reflects a diffuse location of bound DNR.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence anisotropy, r(t), which can decay in time because of the rotational motion of the molecules and consequently leads to depolarization of the fluorescence is fitted to biexponential decay function. The faster time constant indicates the local/inertial motion of the probe and the slower one reveals the overall tumbling motion of the entire protein (47). The estimated rotational time constant (τ) for the repressor associated with the overall λ-repressor tumbling is estimated to be 27 ns using the Stokes-Einstein-Debye (SED) equation (48).…”
Section: Differential Picosecond-resolved Dynamics Of λ-Repressor Promentioning
confidence: 99%
“…[2][3][4][5][6]. These have shown the influence of the biological nanocavities not only on the diffusional/orientational motions of the drug, but also on its solvation dynamics and excited state processes such as energy, electron and proton transfer.…”
Section: Introductionmentioning
confidence: 99%